Occurrences, sources, and transport of hydrophobic organic contaminants in the waters of Fildes Peninsula, Antarctica. (October 2018) - Gao, Xiaozhong; Huang, Chao; Rao, Kaifeng; Xu, Yiping; Huang, Qinghui; Wang, Feng; Ma, Mei; Wang, Zijian
Abstract: As a pristine continent, Antarctica provides a good opportunity to study the spatial transport and temporal accumulation of environmental contaminants and the impacts of anthropogenic activities, both of which have given rise to ongoing public concern. In this research, an approach of coupling aquatic time-integrated passive sampling with chemical analysis and bioassays was used to assess pollution by hydrophobic organic contaminants in Antarctic waters. Passive samplers were deployed in waters of Fildes Peninsula, Antarctica, and their extracts were used for chemical analyses of sixty-six hydrophobic organic contaminants belonging to five groups [organophosphorus flame retardants (PFRs), phthalic acid esters (PAEs), polycyclic aromatic hydrocarbons (PAHs), organochlorine pesticides (OCPs), and polychlorinated biphenyls (PCBs)] and in vitro bioassays for endocrine disruption and genotoxicity. In total, twenty pollutants (six PFRs, one PAE, two PAHs, six OCPs, and five PCBs) were quantified, and six PFRs had concentrations that ranged from ND (not detected) to 44.37 ng L −1 in Antarctic waters. The concentrations detected in the waters were generally low and insufficient to have significant in vitro endocrine disruption potential or genotoxicity. The source and transport pathways of PFRs and PAE in Fildes Peninsula were studied, and multiple local sources (wastewater, air traffic, research stations, and animal feces) for different PFRs were proposed. A spatial and temporal analysis showed slight changes in the exposure of OCPs and PCBs in Antarctic waters. Furthermore, a comparison among a variety of Antarctic water sampling cases revealed that passive sampling can be a tool for aquatic time-integrated investigations in polar regions. Graphical abstract: Highlights: Antarctic waters were investigated by passive sampling coupled with bioassays. Six organophosphorus flame retardants (PFRs) were identified in Antarctic waters. Antarctic anthropogenic and biological activities led to different PFR exposure. Abstract : Six organophosphorus flame retardants were identified in Antarctic waters and the exposures are led by different anthropogenic and biological activities.